INSECTS OF THE SURKHAN STATE SANCTUARY (INSECTA: LEPIDOPTERA) (Scientific journal of the Fergana State University, 2024)
In this article, information is provided about the horned insects found in the Khatak, Sherjan and Khojango sections of the Surkhan State Reserve. As a result of the research, 8 species of the Nymphalidae family, 6 of the Pieridae family, 4 of the Lycaenidae family, 2 of the Hesperiidae family, 3 of the Sphingidae family, 2 of the Papilionidae family, 1 of the Saturnidae, Crambidae, and Geometridae families were recorded in the biotopes of the research area. At the same time, the trophic relationships of pinworms with food plants have been revealed.